2021
DOI: 10.1021/acs.jchemed.1c00846
|View full text |Cite
|
Sign up to set email alerts
|

OrgoPrep: A Remote Peer-Led Summer Program Preparing Students for Organic Chemistry

Abstract: The transition from general chemistry to organic chemistry is challenging for many students. To succeed, students must remember their foundational chemistry skills and effectively transfer that knowledge into the context of organic chemistry. However, this transition is often hindered by many obstacles: (1) lack of prerequisite knowledge, (2) lack of understanding how foundational chemistry knowledge is applicable to organic chemistry, and (3) high levels of anxiety and low levels of self-efficacy toward organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…OrgoPrep students outperformed those who did not participate in the program by over half a letter grade ( d = 0.573, p < 0.001). These benefits were even larger in 2021 than in the pilot year of the program . Furthermore, OrgoPrep students performed better than their non-OrgoPrep counterparts on all five exams in organic chemistry, including the cumulative final exam, with effect sizes ranging from d = 0.478 to 0.579 ( p < 0.001).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…OrgoPrep students outperformed those who did not participate in the program by over half a letter grade ( d = 0.573, p < 0.001). These benefits were even larger in 2021 than in the pilot year of the program . Furthermore, OrgoPrep students performed better than their non-OrgoPrep counterparts on all five exams in organic chemistry, including the cumulative final exam, with effect sizes ranging from d = 0.478 to 0.579 ( p < 0.001).…”
Section: Resultsmentioning
confidence: 92%
“…Since achievement gaps are especially wide in organic chemistry, past studies have explored if summer preparatory programs could enhance the transition between general and organic chemistry courses and minimize attrition. , One such asynchronous program utilizing lecture-style instructional videos, accompanying notes, and online assignments was shown to benefit all students equally, including those identified as low-income, first-generation, or underrepresented minorities. Although this program was successful in improving organic chemistry performance by about a third of a letter grade, no differential impact for HMGs was observed, and pre-existing achievement gaps were perpetuated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of PLTL has been shown to improve exam scores (Tien et al, 2002) and lead to higher success rates (Wamser, 2006) in organic chemistry. Online preparatory courses (Fischer et al, 2019;Pulukuri et al, 2021) delivered via a learning management system have also been found to result in higher performance and success rates in organic chemistry. There are also various examples of utilizing social-psychological interventions (SPIs) in order to increase performance and persistence in STEM courses.…”
Section: Discussionmentioning
confidence: 99%
“…Question-embedded videos (QEVs) are asynchronous learning tools that require students to solve problems and receive targeted feedback throughout the video. By design, embedded problems enforce student engagement and trigger active learning. While QEVs can serve as standalone instructional resources, they are also effective learning modalities for the preclass preparation phase of flipped classrooms. ,, Prior research suggests that students learn more in the independent and asynchronous preparation phase of a flipped classroom, so finding effective out-of-class teaching methods is critical for maximizing learning gains and promoting equitable learning environments. Although textbook readings have traditionally been the primary out-of-class learning resource, instructors have been transitioning to using traditional narrative videos, such as those posted on YouTube or Khan Academy, instead.…”
Section: Introductionmentioning
confidence: 99%